Synthesis of nZVI-Ni@BC composite as a stable catalyst to activate persulfate: Trichloroethylene degradation and insight mechanism. Issue 1 (February 2021) - Shan, Ali; Idrees, Ayesha; Zaman, Waqas Qamar; Abbas, Zain; Ali, Meesam; Rehman, Muhammad Saif Ur; Hussain, Sabir; Danish, Muhammad; Gu, Xiaogang; Lyu, Shuguang
Graphical abstract: Highlights: Synthesis of the nZVI-Ni@BC composites to activate persulfate for TCE degradation. Excess oxygen functional groups and abundant active sites of nZVI-Ni@BC efficiently activated persulfate. SO4 ˉ and OH have dominant roles for complete removal of TCE in the nZVI-Ni@BC-persulfate system. In the nZVI-Ni@BC-persulfate system acidic solution was favorable for the removal of TCE. High level of CO3 2 ¬, HCO3 ˉ, and NOM inhibited the overall persulfate oxidation of TCE. Abstract: In Fenton-like oxidation processes, the use of biochar (BC) as support material for the nanoscale zero valent iron-nickel (nZVI-Ni) bimetallic particles attained much attention to activate persulfate (PS) for TCE degradation in aqueous medium. In present work, nZVI-Ni@BC particles with nZVI-Ni to BC mass ratio of 1:5 exhibited excellent results (> 99 % ± 0.24) for TCE degradation. The physico-chemical characteristics, surface morphologies, and elemental mapping of the synthesized nZVI-Ni@BC particles investigated through SEM, EDX, TEM, XPS, XRD, BET and FTIR spectroscopy. For the nZVI-Ni@BC-persulfate system, the effects of PS concentration, initial pH, inorganic ions and natural organic matter (NOM) on TCE degradation were evaluated. Batch experiments revealed that complete removal of TCE (> 99 % ± 0.25) was attained at 250 mg L −1 of nZVI-Ni@BC and 4.0 mM PS dosages at pH 3.49 ± 0.55. Scavenging and electron paramagnetic resonance (EPR) verified the dominant role of both SO4 ˉ and OH radicals in acidic environment for degradation of TCE. Moreover, high level of carbonate, bicarbonates and NOM inhibited the overall TCE oxidation reaction. In summary, these results suggested that nZVI-NI@BC composite was an alternative, economic and promising catalyst for the activation of PS to degrade chlorinated contaminants in aqueous medium.